IMPLEMENTATION OF ANALYSIS OF THE MC CALL MODEL ON THE WEBSITE OF LUBUKLINGGAU CITY LIBRARY AND ARCHIVES SERVICE (Departement Information Systems Universitas Kebangsaan Republik Indonesia, 2023)
The library is used to find references and information. The problem faced is that some libraries do not yet have an online Web-based system to find sources of learning information. Technological developments are expected to provide benefits for library management. The background of this research is that libraries are expected to be able to take advantage of the technological developments in web-based systems to find sources of learning information. Technological developments are expected to provide benefits for library management. The background of this research is that libraries are expected to be able to take advantage of technological developments. By using the McCall method, the website, which is in the library and archives office in the city of Lubuk linggau, will assist the community in finding references and information optimally to meet their needs. The purpose of this study was to find out how the McCall Model was implemented and what percentage of people used the Infinite website for the library and archives service in the city of Lubuk linggau. Researchers used a quantitative approach with the McCall analysis version. Then this study uses two stages: the first is an instrument test technique in the form of a validity and reliability test, and the second is software quality. The McCall model technique is operational in software programs (product operations), with several quality factors, namely truth, reliability, usability, integrity, and efficiency. The results of this study are the measurement process using the MC call method involving 60 respondents, and the measurement results of this analysis obtain a total quality percentage. Corerecnes: 60.1% (good) Reliability: 50.1% (good enough) Usability is 60.1% (good), integrity is 99.6% (very good), and efficiency is 69.6% (good).